Actual Problems of Creating Digital Twins of Machine Engineering Products in Terms of Durability Assessment - Erpalov, A. V.; Khoroshevskii, K. A.; Gadolina, I. V. (Inorganic materials, 2024)
The global digitalization of production opens new opportunities for predictive diagnostics of the technical condition of mechanical engineering products. The issues attributed to assessing their technical condition, primarily to the determination of the residual life of mechanical engineering products, are considered. Currently, a class of virtual models, digital twins of the residual life, is distinguished. Apart from the functions of monitoring and predicting the stability of structures, they can possess a feedback and control the durability by simulating and optimizing the real technological process, taking into account the possibility of achieving the limit state of the structure. The problems of existing methods of assessing the durability in the time and frequency domains are considered in detail from the viewpoint of using the residual resource of structures as the basis of an algorithmic support of digital twins. We also marked the possible variety of obtaining initial data for assessing the durability, namely, fatigue diagrams of materials for different types and schemes of loading. The fatigue diagram is greatly affected by the loading process (regular, random, or mixed), while in the actual work the nonstationary random loading prevails. The methods used for assessing the durability of nonstationary loading are poorly studied and often resolve into simplification of a nonstationary process. The study is focused on nonstationary loading processes, since the creation of digital twins implies a continuous analysis of the durability of the structure for real operational loads. Other problems that can arise when developing digital twins of structures are also considered and discussed.